Pengembangan LKS Berbantuan Media Electronic Workbench untuk Meningkatkan Nilai Karakter Siswa pada Bahasan Listrik Dinamis - Setiawan, Rendy; Susilo, Susilo (UPEJ Unnes Physics Education Journal, 2017)
The availability of the media supporting learning, minimal inhibiting the creation of effective learning activity. To overcome the lack of availability of laboratory tools at SMK Muhammadiyah Kradenan electric circuit experiments especially in dynamic, used software called Electronic Workbench 5.12 developed in is categorized. The method in this research is R&D. Order categorized created contains an introduction, a summary of the dynamic electrical material, guide students do practical applications using EWB, bibliography of references that have been used in the preparation of categorized as well as profile the application of EWB. Feasibility test and analysis of readability stated that is categorized as very viable to use and easy to understand. Cognitive value analysis results using test students gain obtained an increase of 0.21 low criteria. The value of the character of the discipline, communicative, curiosity, creative and start expanding at an increase of 0.13 berkriteria low. Analysis results can be drawn conclusions if categorized media assisted can improve cognitive values and character but not significantly